Cardiac Steatosis in HIV-A Marker or Mediator of Disease? - Jacob, Morgan; Holloway, Cameron J. (Frontiers in Endocrinology, 2018)
Although people living with HIV (PLHIV) are approaching normal life expectancy, a limitation to achieving this goal is managing the higher prevalence of co-morbidities, including cardiovascular disease. Whilst ischaemic heart disease likely contributes to a large proportion of cardiac disease in the modern era of treatment, cardio-metabolic disease, including cardiac steatosis, akin to obesity-related heart disease, is also a possible mechanism of increased cardiac morbidity and mortality. HIV and other metabolic and inflammatory diseases affecting the heart, including obesity, share many cardio-metabolic abnormalities, with increased pericardial and myocardial fat content, in association with chronic systemic inflammatory changes and alterations in cardiac metabolism. Understanding the mechanisms of HIV-associated cardiac steatosis remains an important challenge, as managing the untreated metabolic and inflammatory precipitants may substantially improve cardiac outcomes for PLHIV.